The Safety Profile of Single Daily Dose of Aminoglycosides in Comparison with Multiple Daily Dose - A. Baker, Amanj; A. Majeed, Ibrahim; K. Ismail, Dawser (Iraqi Journal of Pharmaceutical Sciences, 2017)
To overcome the problems which associated with the standard multiple daily doses (MDD) of aminoglycosides (AGs) like high incidence of toxicity(nephrotoxicity, ototoxicity)(5-25%) and high cost, an alternative approach was developed which was single daily dose (SDD).This new regimen was designed to maximize bacterial killing by optimizing the peak concentration/minimum inhibitory concentration(MIC)ratio and to reduce the potential for toxicity. The study includes 75 patients selected randomly, 50 of them received SDD regimen of age range of 17-79 years and the remaining received MDD regimen of age range of 13-71 years. The study was designed to evaluate the safety of SDD regimen in comparison with MDD regimen. All the patients in SDD group received a constant dose of 5-mg/kg/day of gentamicin and 20mg/kg/day of amikacin with a drug administration interval based on estimated creatinine clearance(CLcr): if ≥60 ml//min every 24 hours (q24h), 59- 40 ml/ min every 36hours and 39- 30 ml/min every 48 hours.The calculated dose was diluted with 0.9% normal saline or 5% dextrose to 50-100 ml and given as intravenous infusion over 30-60 minutes. In SDD group , the mean length of therapy was 6.4±1.73 days .Gentamicin accounted for 96% of the aminoglycoside use, and the majority(58%) of patients received the drug every 24 hours.The 36- and -48 hours intervals were used for 34 and 8% of the population, respectively.While in MDD group , the mean length of therapy was 5.0±0.91 days. Gentamicin accounted for all (100%) of aminoglycoside use, and all of the patients received the drug every 8 hours. No clinically apparent ototoxicity and nephrotoxicity were observed in the patients in the SDD group, in contrast to the patients in MDD group, in whom 4 patients (16%) were developed nephrotoxicity and 1 patient (4%) was developed ototoxicity. The obtained results indicate that SDD regimen was safer through decreasing the incidence of both nephrotoxicity and ototoxicity.For statistical analysis, ANOVA test was used with P<0.01.Each mean was expressed as mean±SEM(Standard Error of Mean). Key words: Aminoglycosides, Single Daily Dose, Nephrotoxicity and Ototoxicity.